Deteksi Ekspresi Protein Wnt4 pada Uterus Mencit (Mus musculus L.) dengan Metode Immunohystochemistry - Sitasiwi, Agung Janika (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Study to detect the expression of Wnt4 protein in the uterus of Swiss Webster mice with immunohistochemistry method has been done. Laboratory animals that were used are adult Swiss Webster mice weighing 25-30 grams. Pregnancy is determined by the presence of vaginal plug in female mice after breeding. Uterus was isolated on seventh days of gestation. The detection of protein expression was done by paraffin method using mouse anti-Wnt4 (Santa Cruz Biotechnology) as primary antibody with 1:250 in dilution. Visualization of Wnt4 protein was done by DAB as chromogen. The positive reaction to the primary antibody showed in perimetrium, myometrium, and endometrium in uterine tissue. The positive reaction to the primary antibody were expressed on blood vessels also. It could be concluded that the Wnt4 protein as signal molecule regulates the embryo development by circulation system. This study offer as source to study Wnt4 protein expression pattern as molecular marker in early development of organism. Â Keywords: Wnt4, immunohystochemistry, Mus musculus